2018
DOI: 10.1097/nne.0000000000000494
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Innovation to Redesign the Baccalaureate Curriculum to Address Population Health

Abstract: Prelicensure nursing curricula need to be redesigned to integrate and achieve key population health competencies. Nursing students in generic and second-degree programs had improved learning outcomes and significant increases in population health competencies across the curriculum using simulation-based learning activities developed through an academic-practice partnership. Simulation is an effective, interactive strategy that enhances student knowledge, skills, and competencies in addressing population health. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Simulated participants (SP's) including on-line formats ( Min-Yu Lau et al, 2016 ;Weideman et al, 2016 ) was the most frequently reported SBL modality (n = 13/43%). High-fidelity manikin-based SBL was used in seven studies (23%), as either the sole modality or in conjunction with video vignettes/recorded SP encounters ( Fioravanti et al, 2018 ;Harder, 2018 ;Mauro et al, 2018 ) or student/faculty roleplay ( Garrido et al, 2016 ;Grossman et al, 2012 ).…”
Section: Simulation Modalitymentioning
confidence: 99%
See 3 more Smart Citations
“…Simulated participants (SP's) including on-line formats ( Min-Yu Lau et al, 2016 ;Weideman et al, 2016 ) was the most frequently reported SBL modality (n = 13/43%). High-fidelity manikin-based SBL was used in seven studies (23%), as either the sole modality or in conjunction with video vignettes/recorded SP encounters ( Fioravanti et al, 2018 ;Harder, 2018 ;Mauro et al, 2018 ) or student/faculty roleplay ( Garrido et al, 2016 ;Grossman et al, 2012 ).…”
Section: Simulation Modalitymentioning
confidence: 99%
“…Others involved a Somalian cultural-broker who shared personal insights into female genital mutilation/cutting ( Jacoby & Smith, 2013 ) and community agency representatives in an established table-top poverty simulation ( Yang et al, 2014 ). While the extent of involvement was largely unclear, studies also referred to scenario cocreation in conjunction with culturally diverse SP's ( Min-Yu Lau et al, 2016 ;Ndiwane et al, 2014 ;Weideman et al, 2016 ) or students ( Garrido et al, 2014 ), while some utilized external consultants ( Mauro et al, 2018 ) or education/simulation experts ( Byrne, 2020 ;Fioravanti et al, 2018 ;Lin & Hsu, 2020 ;Maruca et al, 2018 ) in the development and/or review of scenarios.…”
Section: Cultural Authenticity and Fidelitymentioning
confidence: 99%
See 2 more Smart Citations
“…HFPS simulates realistic clinical situations (Adamson, 2015; Cant & Cooper, 2017; Jeffries, 2012) and prepares students for clinical tasks with no risk to the safety of actual patients as opposed to low fidelity patient manikins (LFPM) (Adamson, 2015; K. S. Dunn, 2017; Jeffries, 2012; Kaddoura et al, 2016; Mauro et al, 2017; Richardson & Claman, 2014).…”
Section: Introductionmentioning
confidence: 99%